Leader´s and Ceo´s background and its impact on performance: evidence from the world of football - Monteiro, Tomás Melo De Carvalho Amaro (2022)
This paper tries to measure to what extent does CEO/Presidents’background and characteristics in Football affect the performance of their Clubs. To do so, a sample covering the last 50 years’ presidents of 28clubs from the 5 best leagues in Europe was gathered, in a total of 203 presidents and 1428 observations. Through four time/club fixed effects regressions, the impact of variables such as Tenure, Sports Industry Experience, Academic Degrees and Functional Backgrounds, on both Clubs’ Titles and Classifications,was measured and the results discussed.